2005
DOI: 10.1007/s00439-005-0046-4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial polymorphisms and susceptibility to type 2 diabetes-related traits in Finns

Abstract: Mitochondria play an integral role in ATP production in cells and are involved in glucose metabolism and insulin secretion, suggesting that variants in the mitochondrial genome may contribute to diabetes susceptibility. In a study of Finnish families ascertained for type 2 diabetes mellitus (T2DM), we genotyped single nucleotide polymorphisms (SNPs) based on phylogenetic networks. These SNPs defined eight major haplogroups and subdivided groups H and U, which are common in Finns. We evaluated association with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
59
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 57 publications
8
59
2
2
Order By: Relevance
“…So, haplogroup T has also been found to significantly protect against type 2 diabetes in a very distant Russian population study (Buikin et al, 2008). Haplogroup J showed a trend toward association with type 2 diabetes in Finns (Mohlke et al, 2005) and JT in Caucasian-Brazilians (Crispim et al, 2006). Furthermore, it is subclade J1 that seems to confer susceptibility to the same illness in Jewish patients with diabetes-affected parents (Feder et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, haplogroup T has also been found to significantly protect against type 2 diabetes in a very distant Russian population study (Buikin et al, 2008). Haplogroup J showed a trend toward association with type 2 diabetes in Finns (Mohlke et al, 2005) and JT in Caucasian-Brazilians (Crispim et al, 2006). Furthermore, it is subclade J1 that seems to confer susceptibility to the same illness in Jewish patients with diabetes-affected parents (Feder et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In other instances, different mtDNA backgrounds seem to partially explain the different ethnic or geographic predispositions to diabetes (Tajima et al, 2004). This could be one of the causes to explain the fact that the mtDNA T16189C transition has been consistently associated with type 2 diabetes susceptibility in Asia (Park et al, 2008) but only sporadically in Europe (Poulton et al, 2002;Chinnery et al, 2005), or that some specific Western Asian mtDNA haplogroups, such as J, seem to confer susceptibility to type 2 diabetes in Finns (Mohlke et al, 2005) and Caucasian-Brazilians (Crispim et al, 2006), but this trend could not be detected in other large European samples (Saxena et al, 2006;Chinnery et al, 2007;Benn et al, 2008). In this regard, it seems pertinent to point out that the present-day Canarian inhabitants represent a mixed population made up by pre-Hispanic natives of North African origin and mainland colonizers from the Iberian Peninsula (Flores et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, a meta-analysis of studies in European populations suggested it was unlikely that the region containing the mt16189 polymorphism played a role in increasing susceptibility to type 2 diabetes [16]. One of the largest studies to date, carried out in the Finnish population, confirmed the association with mt16189, and also reported a weak association with haplogroup J [17]. This is the first reported association with a major haplogroup.…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, a variant at position 16189 has been shown to be associated with elevated fasting insulin concentrations (Poulton et al, 2002;Poulton et al, 1998) and Type 2 Diabetes in a population-based casecontrol study (Poulton et al, 2002). However, other studies have been unable to replicate this association (Chinnery et al, 2005;Das et al, 2007;Mohlke et al, 2005). Moreover, another study aimed to capture the entire common variation (except the hypervariable D-loop) in mtDNA with a frequency >1%, and test if any of these variants are associated with Type 2 Diabetes (Saxena et al, 2006); 3304 cases and 3304 matched control subjects were examined.…”
Section: Genetic and Epigenetic Regulation Of Mitochondria And Associmentioning
confidence: 99%